Organizacja sieciowo-wirtualna a wirtualizacja funkcji personalnej - Antczak, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The author presents the unique results of research on personnel function in virtual network-based companies. Following these changes among other things virtualization of personnel function was diagnosed (e-Human Resources Management). It should be expected that Polish managers, either working in corporate enterprises or competing with them and observing solutions which are used there, learn to function in the realities of global knowledge society. Therefore, they will assimilate and adopt concept of virtual-network companies and virtualization of personnel function (e-HRM) to conditions they will have to take actions in. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 11-19